2017
DOI: 10.1093/cid/cix443
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Impairment of Voriconazole Clearance by High-Dose Meropenem in a Patient With Renal Failure

Abstract: A critically ill patient with multiple postoperative infections repeatedly required profound voriconazole dose reductions whenever high-dose meropenem was added. Subsequent in vitro assessment confirmed inhibition of cytochrome P450 (CYP) 2C19 and CYP3A4 by meropenem, suggesting that during meropenem treatment, narrow therapeutic index drugs metabolized by these CYPs require close monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Twenty articles that met the inclusion criteria were reviewed and the results showed that the VRZ C min and CRP-level curves were highly consistent, suggesting that VRZ concentration was significantly correlated with the level of inflammation in the body. 44,45 The effect of inflammation on VRZ metabolism appears to be more prominent with age. 44,45 The results of two studies on children also showed that the effect of the inflammatory state on VRZ metabolism in children needs to be analysed along with age groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty articles that met the inclusion criteria were reviewed and the results showed that the VRZ C min and CRP-level curves were highly consistent, suggesting that VRZ concentration was significantly correlated with the level of inflammation in the body. 44,45 The effect of inflammation on VRZ metabolism appears to be more prominent with age. 44,45 The results of two studies on children also showed that the effect of the inflammatory state on VRZ metabolism in children needs to be analysed along with age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty articles that met the inclusion criteria were reviewed and the results showed that the VRZ C min and CRP‐level curves were highly consistent, suggesting that VRZ concentration was significantly correlated with the level of inflammation in the body 44,45 . The effect of inflammation on VRZ metabolism appears to be more prominent with age 44,45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a report that high-dose meropenem inhibits CYP2C19 and CYP3A4. [14] So high-dose meropenem can potentially change the exposure of rivaroxaban metabolized by CYP3A4. But this patient was on conventional-dose meropenem; there may be no drug interaction between meropenem and rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Mahmoudi and co-workers reported the case of a critically ill patient which repeatedly required profound voriconazole dose reduction when high-dose meropenem was added [ 46 ]. The authors also performed in vitro assessments providing for the first time evidence that meropenem may inhibit the CYP2C19 and CYP3A4 isoforms.…”
Section: Antibiotics As Victims or Perpetrators Of Pddismentioning
confidence: 99%